Burkitt lymphoma-a retrospective analysis of data from the Registry of the Czech Lymphoma Study Group with external validation of the Burkitt lymphoma International Prognostic Index - Sýkorová, Alice; Procházka, Vít; Móciková, Heidi; Janíková, Andrea; Pytlík, Robert; Belada, David; Benešová, Kateřina; Klener, Pavel; Ďuraš, Juraj; Smolej, Lukáš; Campr, Vít; Blahovcová, Petra; et al. (Neoplasma, 2022)
Burkitt lymphoma (BL) is a rare subtype of non-Hodgkin's lymphoma with an aggressive course. To refine the individual patient's prognosis, the International Prognostic Index for BL (BL-IPI) was recently developed and 4 risk factors (RF) were determined as optimal prognostic cut-off by multivariate analysis: age ≥40 years, lactate dehydrogenase >3× upper limit of normal, ECOG performance status ≥2, and central nervous system involvement. The BL-IPI distinguishes 3 prognostic groups, low (without RF), intermediate (1 RF), and high risk (2-4 RF), with significant differences in survival. The aim of the current project was to perform an external validation of the BL-IPI in 101 patients from the Registry of Czech Lymphoma Study Group diagnosed between 1999 and 2016 (median age, 45 years). The median follow-up was 50.4 months. The induction treatment included rituximab plus chemotherapy in 82% and chemotherapy alone in 18%. The overall response rate was 78% and the complete remission rate was 73%. According to BL-IPI, low/intermediate/high risk was present in 21/35/45% of patients, showing high similarity to the training BL-IPI US (United States) dataset (18/36/46%). There were significant differences in progression-free survival (PFS) and overall survival (OS) between patients with high vs. intermediate risk (PFS: hazard ratio 0.16, 95% confidence interval 0.08-0.31, p<0.0001; OS: hazard ratio 0.17, 95% confidence interval 0.09-0.35, p<0.0001) but not between patients with low vs. intermediate risk. The 3-year OS probability according to BL-IPI with low/intermediate/high risk was 96/76/59% in the BL-IPI training dataset vs. 95/85/45% in our external validation cohort; the 3-year PFS probability with low/intermediate/high risk was 92/72/53% in the BL-IPI training dataset vs. 95/85/42% in our cohort. In summary, our external validation of the BL-IPI confirmed a good separation of high-risk patients, who have a poor prognosis and for whom the new therapeutic approaches are needed; patients with low and intermediate risk had favorable clinical outcomes, and differences between these groups were not significant, likely due to a small number of patients.
Keywords: difúzní velkobuněčný B-lymfom; Retrospective Studies; Prognosis; Burkittův lymfom; Česká republika; Middle Aged; registrace; Adult; Burkitt Lymphoma; Czech Republic; Registries; Lymphoma, Large B-Cell, Diffuse; prognóza; retrospektivní studie; Humans; lidé středního věku; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; dospělí; lidé